SOLVE MOVEMENT PROBLEMS IN A VARIETY OF WAYS - Umarova Guzalkhon Botirjonovna, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The paper deals with motion problems, the problem of finding the connections between the three quantities that characterize motion — velocity, time, and distance — in which the said quantities participate as directed quantities. It is considered that the quantities that characterize the motion, that is, the problems involving speed, time and distance, are problems of motion.